조직공학적연골재생에 있어서 세포유래 세포외기질(ECM) 지지체의 응용 - 김성철 (The Graduate School, Ajou University, 2007)
In recent years, cartilage tissue engineering for reconstruction or repair of a cartilage injury has been emerged as alterative solutions based on the application of selected chondrocytes and scaffold. The purpose of present study is to evaluate the feasibility of novel cell-derived extracellular matrix (ECM) scaffold on cartilage tissue engineering in vitro and in vivo as nude mouse and rabbit model. Chapter I: A porous cell-derived ECM scaffold was prepared with a freeze-drying protocol using porcine chondrocytes. The ECM scaffold had highly uniform porous microstructure by scanning electron microscope (SEM). It showed an average pore diameter of 504±108um, a porosity of 90±10.4%, a surface area of 905±204 m2/g and a tensile strength of 0.34±0.09 MPa, respectively. In vitro study, Then, rabbit chondrocytes were seeded dynamically on the ECM scaffold and cultured for 2 days, 1, 2 and 4 weeks in vitro for analysis. The neocartilage-like tissue was observed after 1 week of culture, and the volume and compressive strength were significantly increased with culture time. The DNA, glycosaminoglycan (GAG) and collagen contents also increased gradually with time. Histological staining for GAG (Safranin O staining) and type II collagen (immunohistochemistry) showed sustained accumulation of the ECM molecules along with time, which gradually and uniformly filled the porous space in the ECM scaffold. Chapter II: In vivo study as nude mouse, cell-seeded ECM scaffold was cultured for 2 days in vitro, and then implanted into the nude mouse subcutaneously. They were retrieved at 1, 2, and 3 weeks post-implantation. Under macroscopic analysis, the cartilage-like tissue formation matured by time and developed a smooth, white surface. And, the size of the neocartilage tissue increased slightly by the 3rd week and remained more stable. Total GAG content and the GAG/DNA ratio increased significantly by time in the chemical analysis. The histology exhibited a sustained accumulation of newly synthesized sulfated proteoglycans. Immunohistochemistry, Western blot, and RT-PCR clearly identified type II collagen at all time points. Compressive strength of in vivo neocartilage increased from 0.45±0.06MPa at 1 week to 1.18±0.17MPa at 3 weeks. Chapter III: In vivo study as rabbit model, the knee defects were implanted with in vitro cultured tissue engineering cartilage using ECM scaffold and allogenic rabbit chondrocytes as 2days, 2, and 4 weeks (experimental group 2, 3, and 4), respectively. The left knee defects were not implanted as control (group 1). The maturity of cultured implants was evaluated by histological, chemical and mechanical assay in chapter I. The repair examination was evaluated with macroscope and histological assay at 1 and 3 months post-surgery. After 1 month, fibro/hyalinecartilge was found on histological examination in the group 1, 2 and hyalinecartilage was found in group 3, 4. However, a mature matrix and a columnar organization of chondrocytes can be observed with Saflanin-O staining in group 4 at 3 months. Moreover, the subchondral bone was well remodeled and the more type II collagen was expressed at that time in the group 4. Thus ICRS histological score were significantly increased in the group 4 at that time. In conclusion, this study demonstrated that the novel cell-derived ECM scaffold could provide a promising environment for generating a high quality cartilage in vitro and in vivo as nude mouse. Moreover, the engineered cartilage using the cell-derived ECM scaffold and allogenic chondrocytes could regenerate the cartilage defects particularly when cultured mature cartilage provided better results.
학위논문(박사)----아주대학교 일반대학원 :의학과,2007. 8
Keywords: cell-derived extracellular matrix (ECM) scaffold; chondrocyte; tissue engineering cartilage; vitro; vivo